Pengembangan Lembar Kerja Siswa Tematik Tema Indahnya Persahabatan Berbasis Inkuiri Terbimbing di Kelas III SDN Polisi 4 - Candraini, Hesti; Hayu, Wiworo Retnadi Rias; Kurniawati, Atin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to develop and test the feasibility of Thematic Student Worksheets (LKS) based on Guided Inquiry as a handbook or self-learning material for third-grade students on the theme of Beautiful Friendship, with the sub-theme of Plant Friends in the 2013 Curriculum. The main material of the LKS includes friendship towards all living beings. This research is a type of R&D research adopting the 4D model development steps, but in this study, only 3D was used, namely: Define, Design, and Develop. The research instrument used is a product validation questionnaire conducted by one expert, one material expert, and three elementary school teachers. Product trials were conducted on third-grade students at SDN Polisi 4 Bogor, with 6 students as individual trial subjects and 28 students as limited trial subjects. Data analysis used quantitative and qualitative methods using a Likert scale. The result of this research is the